If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -3 + 2x = 8x Reorder the terms: -3 + 4x + 2x = 8x Combine like terms: 4x + 2x = 6x -3 + 6x = 8x Solving -3 + 6x = 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -3 + 6x + -8x = 8x + -8x Combine like terms: 6x + -8x = -2x -3 + -2x = 8x + -8x Combine like terms: 8x + -8x = 0 -3 + -2x = 0 Add '3' to each side of the equation. -3 + 3 + -2x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -2x = 0 + 3 -2x = 0 + 3 Combine like terms: 0 + 3 = 3 -2x = 3 Divide each side by '-2'. x = -1.5 Simplifying x = -1.5
| 6+k=14 | | (2x^2+3x-2)(3x^2-6x-5)= | | n-4=24 | | 23=-2(24-b)+3(b-3) | | 15x+21(x-2)=318 | | 4x^2+7-3=0 | | 19x-(4x-9)=84 | | 19x-3(4x-9)=84 | | 5m+10=9m-2 | | 5(6z+1)-9=146 | | 3(4x-1)=36 | | (-6)(9)= | | (4-9)= | | 4w^2=-12w-5 | | [10-2]= | | 12*-72= | | 14y=-84 | | v+-391=1255 | | v+-391=255 | | 8(4+4(5))= | | v+255=-391 | | 8(4+5(5))= | | -5(2x+1)=1-4(x+9) | | (x-5)(2x^2+3x-1)= | | 3(x+9)=42 | | X^6+5x^3-6=0 | | x(x)+5x+6=0 | | x(x)-5x-6=0 | | (3x^2-4x+10)-(x^2-9x+13)= | | c+150=1860 | | 5x(x)=6+2x | | x-13=-3 |